Development of cryo-adsorption hydrogen storage systems for ship's PEMFC power units. (January 2022) - Zhang, Xuan; Zheng, Qingrong; He, Hong-zhou; Zhang, Zhong-gang; Sun, Di
Highlights: Toth equation has a higher predicting accuracy than Dubinin-Astakhov equation. Interaction between hydrogen-MIL-101 is stronger than that of hydrogen-SAC-03. Temperature effect of desorption ratio and usable capacity ratio is different. Thermal conductivities of the samples may be the temperature dependent. Abstract: The paper focus on developing hydrogen storage systems for ship's fuel cell power units. Activated carbon SAC-03, MIL-101 and its composite JMU-01 formed by mixing the expanded natural graphite (ENG) in 10 wt% were selected. Adsorption data of hydrogen were measured at a temperature range 77.15 K-87.15 K within pressure 0–6 MPa. Accuracies of results predicted by Toth and Dubinin-Astakhov (DA) equations were evaluated, the isosteric heat of adsorption and the interaction potential were then determined. A conformable vessel that can meet the fuel consumption required by 7.5 kW PEMFC was employed charge and discharge tests at ambient temperature and 77.15 K. Results show that, the isosteric heats of hydrogen adsorption on the SAC-03, MIL-101 and JMU-01 are 4.09 kJ·mol −1 -1.43 kJ·mol −1, 4.20 kJ·mol −1 –1.89 kJ·mol −1 and 4.19 kJ·mol −1 –2.20 kJ·mol −1, interaction potential between hydrogen molecules and SAC-03 and MIL-101 are 32.48 K·k and 41.09 K·k. Results also reveal that the desorption ratio (DR) of SAC-03, MIL-101 and JMU-01 at ambient/77.15 K temperature are respectively 0.83/0.85, 0.74/0.81, 0.85/0.85, and the mean usable capacity ratio (UCR) is respective about 6.55/1.36, 6.08/1.32, 6.02/1.31. It suggests that addition of ENG is beneficial to improving the DR of the adsorbent but has a negative effect on the UCR of the storage vessel, and cryo-adsorption of hydrogen on MOFs is more promising than activated carbons.